DETERMINAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU BALITA DI POSYANDU ANGGREK TROWANGSAN COLOMADU - Yeni Anggraini; Reni Puspita Sari; Uji Utami (Jurnal Ilmiah Maternal, 2020)
ABSTRACTExclusive breastfeeding can prevent infant mortality by 13%. The success of exclusive breastfeeding is influenced by the education, work, knowledge and support of the husband. This study uses a cross sectional approach to the type of observational analytic research. Data is collected by distributing questionnaires to respondents. The population in this study is the mother of children under five in Posyandu Anggrek. The sampling technique is purposive sampling. Based on the bivariate analysis between the level of education and exclusive breastfeeding, the p-value of 0.003 (p 0.05) was obtained, so that a significant relationship was concluded. Based on the bivariate analysis between employment status and exclusive breastfeeding, p-value of 0.035 (p 0.05) was obtained, so that a significant relationship was concluded. Based on the analysis of the level of knowledge with exclusive breastfeeding obtained p-value of 0.027 (p 0.05), so it was concluded that there was a significant relationship. Based on bivariate analysis between husband support and exclusive breastfeeding, p-value of 0.007 (p 0.05) was obtained, so it was concluded that there was a significant relationship.Keywords: Exclusive breastfeeding, Education Level, Employment Status, Knowledge Level, Husband's Support ABSTRAK Pemberian ASI eksklusif dapat mencegah kematian balita sebanyak 13%. Keberhasilan pemberian ASI eksklusif dipengaruhi oleh pendidikan, pekerjaan, pengetahuan dan dukungan suami. Penelitian ini menggunakan pendekatan cross sectional dengan jenis penelitian observasional analitik. Pengambilan data dilakukan dengan membagikan kuesioner kepada responden. Populasi dalam penelitian ini adalah ibu balita di Posyandu Anggrek. Tehnik pengambilan sampel yaitu purposive sampling. Berdasakan analisis bivariat antara tingkat pendidikan dan pemberian ASI Eksklusif didapatkan p-value sebesar 0,003 (p0,05), sehingga disimpulkan terdapat hubungan yang bermakna. Berdasakan analisis bivariat antara status pekerjaan dan pemberian ASI Eksklusif didapatkan p-value sebesar 0,035 (p0,05), sehingga disimpulkan terdapat hubungan yang bermakna. Berdasarkan analisis tingkat pengetahuan dengan pemberian ASI Eksklusif didapatkan p-value sebesar 0,027  (p0,05), sehingga disimpulkan terdapat hubungan yang bermakna. Berdasarkan analisis bivariat antara dukungan suami dengan pemberian ASI Eksklusif didapatkan p-value sebesar 0,007  (p0,05), sehingga disimpulkan terdapat hubungan yang bermakna. Kata Kunci : ASI Eksklusif, Tingkat Pendidikan, Status Pekerjaan, Tingkat Pengetahuan, Dukungan Suami